2016
DOI: 10.1155/2016/7165143
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Reflectarray Antennas: State of Art and New Opportunities

Abstract: Fractal geometries are appealing in all applications where miniaturization capabilities are required, ranging from antennas to frequency selective surfaces (FSS) design. Recently, some fractal patches configurations, giving low losses, reduced size, and quite good phase ranges, have been proposed for the design of reflectarray unit cells. This paper reviews existing fractal-based reflectarrays, highlighting their benefits and limitations. Furthermore, a comprehensive analysis of an innovative reflectarray unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 26 publications
0
30
0
1
Order By: Relevance
“…The above fractal configuration allows to host an electrically longer resonator into a smaller unit cell [18,19], thus offering very appealing miniaturization skills. As a matter of the fact, the combined use of a smaller patch length L and a greater S-value allows to move down the patch resonance frequency, f 0 .…”
Section: Dual-frequency Fractal Unit Cellmentioning
confidence: 99%
“…The above fractal configuration allows to host an electrically longer resonator into a smaller unit cell [18,19], thus offering very appealing miniaturization skills. As a matter of the fact, the combined use of a smaller patch length L and a greater S-value allows to move down the patch resonance frequency, f 0 .…”
Section: Dual-frequency Fractal Unit Cellmentioning
confidence: 99%
“…To this end, a research routine is implemented that fits the desired ϕ nm values onto the simulated phase curves (Figures 5(a)-7(a)), finally returning the corresponding scaling factors S nm or the patch lengths L nm . A more detailed description of the implemented research routine is reported in [13]. Figure 11(e) illustrates the comparison between the radiated H plane patterns.…”
Section: Reflectarray Designsmentioning
confidence: 99%
“…To this end, a modified layout of the fractal unit cell, originally introduced by the authors in [12,13], is investigated and discussed in this paper to increase the unit cell insensitivity to mutual coupling, thus preserving the effectiveness of the infinite array approach, even in the case of highly miniaturized reflectarray cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques have been used in the miniaturization of microstrip patch antennas [7], such as material loading [8,9], shorting and folding [10][11][12][13][14], reshaping [15][16][17][18][19][20], modifying the ground plane [21,22], using metamaterials [23][24][25], and using fractal contours [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%